2015
DOI: 10.1364/oe.23.010075
|View full text |Cite
|
Sign up to set email alerts
|

Diode-pumped actively Q-switched Tm:YAP/BaWO_4 intracavity Raman laser

Abstract: We report an intracavity Raman laser based on BaWO(4) Raman conversion in a diode-pumped actively Q-switched Tm:YAP laser for the first time. With an incident diode power of 17.5 W and a pulse repetition rate of 1 kHz, the maximum average output powers of 880 mW and 306 mW for the fundamental laser at 1.94 μm and the first Stokes laser at 2.36 μm were obtained, respectively. The pulse width and pulse energy of the first Stokes laser were 14.1 ns and 0.31 mJ, respectively. The Raman gain coefficient of the BaWO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Similar calculation, relying on the same method, for the BaWO 4 , yielded a gain coefficient of 1.1 cm/GW for slightly longer wavelength of 1.94 μm [19]. These values show that the gain difference between the KGW and the more popular BaWO 4 becomes less significant in the SWIR region.…”
Section: Discussiomentioning
confidence: 56%
See 1 more Smart Citation
“…Similar calculation, relying on the same method, for the BaWO 4 , yielded a gain coefficient of 1.1 cm/GW for slightly longer wavelength of 1.94 μm [19]. These values show that the gain difference between the KGW and the more popular BaWO 4 becomes less significant in the SWIR region.…”
Section: Discussiomentioning
confidence: 56%
“…information about the obtained output energy. Since 2013, several studies have demonstrated crystalline Raman lasers in the 2 to 4 μm region: A BaWO 4 crystal pumped by a Tm:YAP laser emitting at 2360 nm achieved 0.31 mJ of output energy [19], a YVO 4 crystal pumped by a Tm:YAP laser emitting at 2418 nm yielded 0.27 mJ of output energy [20], a BaWO 4 crystal pumped by a Tm,Ho:GdVO 4 laser emitting at 2533 nm obtained 0.31 mJ of output energy [21,22], a BaWO 4 crystal pumped by a Ho:YAG laser emitting at 2602 nm yielded 0.27 mJ of output energy [23], and a diamond crystal pumped by a tunable OPO around 2.4 µm, emitting from 3.38 to 3.80 μm attained up to 0.12 mJ of output energy [24]. The highest conversion efficiency of these lasers was 13.9% (6.8% efficiency from pump diode, for intracavity lasers).…”
mentioning
confidence: 99%
“…Various approaches have been used to obtain 2.3 μm laser emission. A solid-state Raman laser based on stimulated Raman scattering (SRS) can produce 2.3 μm laser emission [5] . Semiconductor lasers operating near 2.3 μm have been reported [6] .…”
Section: Introductionmentioning
confidence: 99%
“…However, these reports are missing the information about the obtained output energy values. Since 2013, several studies have demonstrated crystalline Raman lasers in the 2-4 µm region: A BaWO 4 crystal pumped by a Tm:YAP laser emitting at 2360 nm achieved 0.31 mJ of output energy [11], a YVO 4 crystal pumped by a Tm:YAP laser emitting at 2418 nm yielded 0.27 mJ of output energy [12], a BaWO 4 crystal pumped by a Tm, Ho:GdVO 4 laser emitting at 2533 nm obtained 0.31 mJ of output energy [13,14], and a BaWO 4 crystal pumped by a Ho:YAG laser emitting at 2602 nm yielded 0.27 mJ of output energy [15]. A more recent publication has introduced a Raman laser based on a diamond crystal, which has the highest Raman gain coefficient, pumped by a Tm:YLF at 1.89 µm emitting at 2.52 µm.…”
Section: Introductionmentioning
confidence: 99%